The Effect of Guided Reading Strategy to the Reading Comprehension of Grade IX Students at SMP Negeri 12 Pematang Siantar on a Narrative Text - Rachel Yolanda Sitepu; Sanggam Siahaan; Bertaria Sohnata Hutauruk (Journal Corner of Education, Linguistics, and Literature, 2023)
The research utilized quantitative research with a quasi-experimental design. A total of 287 students from class IX at SMP Negeri 12 Pematang Siantar was chosen as the population. The sample was split into two classes: the experimental class (IX 1), which had 28 students and used guided reading, and the control class (IX 5), which had 28 students and utilized lectures. The research instruments were pre-test and post-test of multiple choice of narrative text. To process statistical data, the researcher utilized SPSS version 26. The Kolmogorov-Smirnov and Shapiro-Wilk showed results of 0.200 (experimental) and 0.140 (control). The experimental group's post-test mean score exceeded the control group’s post-test by 70 points, leading to the acceptance of the alternative hypothesis and rejection of the null hypothesis. This demonstrates that the guided reading strategy significantly enhances students' narrative text comprehension.